Avaliação das curvas de permanência de longo período e anual, para a estimativa das vazões de referência na bacia hidrográfica do rio Iguaçu - Rosa, Dryelli Alexia Zatta da (2022)
In Brazil, the management of water resources implemented, in 1994, a granting system to release the use of water, which needs to establish water availability based on the hydrological characteristics of the basin over which it affects. Thus, knowing the water conditions of watersheds is important for the management and planning of water resources, providing sustainable development. The current grant system uses minimum reference flows to regulate the flows available in each basin. The present work aimed to compare the reference flows obtained from the FDC, AFDC and the flows obtained through the 7-day moving averages, Q7, by the Weibull distribution, in the Iguaçu River basin. Accordingly, the IC indicator, concavity index, was verified to spatially evaluate the behavior based on the methodologies for obtaining reference flows presented. With the study, it was observed that the reference flows obtained by the AFDC were higher than the reference flows obtained through the long-term permanence curve, and the lowest flows obtained were the reference flows Q7,10. In this way, it is possible to say that the AFDC are able to promote greater flexibility of the grant flows, while if the manager aims to use the Q7,10 or the Q95 obtained by the FDC, there will be a greater restriction of water resources and may interfere in life and economy of users in the region. The application of the Kolmogorov Smirnov test showed that it is possible to use the Weibull equation for minimum flows in the Iguaçu River basin, however the model is much more restrictive than the reference flows obtained by the permanence curves.